Mexico : Selected Issues. (IMF Staff Country Reports; Country Report, 2016)
This Selected Issues paper analyzes transmission of monetary policy rates to lending and deposit rates in Mexico. The results show that transmission of the policy rate to market rates is statistically significant in all cases, except for mortgage rates. For sight deposits, pass-through is low, with a 1 percentage point increase in the policy rate leading to a 0.2 percentage point rise in the deposit rate. For term deposits the pass-through is stronger, but remains below unity at 0.7. The pass-through to both lending and deposit rates is very rapid. The dynamic specifications show that pass-through is significant in either the current or the following month, and the long-term impact is achieved during the second month.